1993
DOI: 10.1007/bf00297552
|View full text |Cite
|
Sign up to set email alerts
|

Junctions between pericytes and the endothelium in rat myocardial capillaries: A morphometric and immunogold study

Abstract: Pericytes are cells of mesodermal origin which are closely associated with the microvasculature. Despite numerous studies little is known about their function. We have studied the relationship between pericytes and the endothelium in rat myocardial capillaries employing ultrastructural and immunogold techniques. 14% of the subendothelial cell membrane is covered by comparatively small pericytic cell processes. About half of these processes are completely embedded in basement membrane material, whereas the rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…AJs are formed by homodimerization of cadherins, with VE-cadherin being the endothelial-specific cadherin. In endothelial cells, it is difficult to distinguish between TJs and AJs, because the two types of structures occur intermingled (25,26). Here we show that p80 and p130 angiomotin are membrane proteins involved in control of permeability in cell-cell junctions but that the effect of angiostatin is limited to inhibiting migration of angiomotin-expressing cells.…”
mentioning
confidence: 69%
“…AJs are formed by homodimerization of cadherins, with VE-cadherin being the endothelial-specific cadherin. In endothelial cells, it is difficult to distinguish between TJs and AJs, because the two types of structures occur intermingled (25,26). Here we show that p80 and p130 angiomotin are membrane proteins involved in control of permeability in cell-cell junctions but that the effect of angiostatin is limited to inhibiting migration of angiomotin-expressing cells.…”
mentioning
confidence: 69%
“…The subendothelial arterial intimal thickness at P L ϭ 150 mmHg is only 20% that at 0 mm Hg. Region TM is not only able to sustain compression due to the porous nature of its fiber matrix, but also to resist stretching due to focal adhesion plaques of integrin origin (7,8) to extracellular matrix fibers between the ECs and the surrounding PCs. EMs shown in ref.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent researchers demonstrated that PCs are highly ramified and in close association with microvessels, including arterioles, capillaries and venules, in virtually every organ and tissue over a wide range of species. Electron microscopy (EM) has demonstrated that PCs have single prominent nuclei and long processes extending circumferentially as well as longitudinally around microvessels and are anchored to the neighboring ECs by adhesion plaques (7,8). PC coverage varies among the types of tissues and microvessels, with overall coverage ranging between 11% in cardiac muscle capillaries to Ϸ50% in the retinal capillaries in rat with more extensive coverage on VMs than capillaries (9).…”
mentioning
confidence: 99%
“…Three types of junctions are found: Adherens junctions [106], tight junctions [41,107,108], and possibly gap junctions [80,[109][110][111].…”
Section: Junctional Complexes At the Bbbmentioning
confidence: 99%